2013
DOI: 10.1371/journal.pone.0077320
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr Induces the Degradation of ZIP and sZIP, Adaptors of the NuRD Chromatin Remodeling Complex, by Hijacking DCAF1/VprBP

Abstract: The Vpr protein from type 1 and type 2 Human Immunodeficiency Viruses (HIV-1 and HIV-2) is thought to inactivate several host proteins through the hijacking of the DCAF1 adaptor of the Cul4A ubiquitin ligase. Here, we identified two transcriptional regulators, ZIP and sZIP, as Vpr-binding proteins degraded in the presence of Vpr. ZIP and sZIP have been shown to act through the recruitment of the NuRD chromatin remodeling complex. Strikingly, chromatin is the only cellular fraction where Vpr is present together… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 64 publications
2
21
0
Order By: Relevance
“…Cell cycle arrest seems to involve Vpr association with the SLX4-SLX1-MUS81-EME1 complex, leading to SLX4 (Structure-specific endonuclease subunit) activation and ultimately proteasomal degradation of MUS81 (Crossover junction endonuclease) and EME1 (Essential Meiotic Structure-Specific Endonuclease 1) [ 127 , 128 ]. Vpr also induces the degradation of multiple other cellular proteins such as the DNA translocase HLTF (Helicase-Like Transcription Factor) [ 171 ], the DNA replication factor MCM10 (Mini Chromosome Maintenance 10) [ 172 ], as well as the chromatin associated proteins ZIP (leucine Zipper), sZIP and class I HDACs (Histone Deacetylase 6) [ 173 , 174 ].…”
Section: Other Cellular Proteins Targeted By the Hijacked Upsmentioning
confidence: 99%
“…Cell cycle arrest seems to involve Vpr association with the SLX4-SLX1-MUS81-EME1 complex, leading to SLX4 (Structure-specific endonuclease subunit) activation and ultimately proteasomal degradation of MUS81 (Crossover junction endonuclease) and EME1 (Essential Meiotic Structure-Specific Endonuclease 1) [ 127 , 128 ]. Vpr also induces the degradation of multiple other cellular proteins such as the DNA translocase HLTF (Helicase-Like Transcription Factor) [ 171 ], the DNA replication factor MCM10 (Mini Chromosome Maintenance 10) [ 172 ], as well as the chromatin associated proteins ZIP (leucine Zipper), sZIP and class I HDACs (Histone Deacetylase 6) [ 173 , 174 ].…”
Section: Other Cellular Proteins Targeted By the Hijacked Upsmentioning
confidence: 99%
“…Host CRL4 complexes are required for the recognition of UV-DNA damage in the absence of viral infection [ 21 , 112 , 113 ], and indeed Vpr expression arrests cell cycle progression at the G2 phase, in a similar manner to a DNA-damage related checkpoint [ 114 ]. In recent years, several putative substrates of Vpr containing CRL4 complexes have been identified, [ 61 , 115 , 116 , 117 , 118 , 119 , 120 ] with uracil DNA glycosylases (UNG2 and SMUG1) being the first recognized [ 118 , 119 ]. Yet, the significance of these Vpr interactions in the context of cell cycle arrest or viral infection is not clear.…”
Section: How Do Viruses Affect Crls?mentioning
confidence: 99%
“…Some studies have suggested that Vpr is also an early viral protein because it is included in the infecting virion before de novo expression from proviral DNA (Maudet et al, 2013). Studies have shown that Vpr can induce neuronal apoptosis indirectly by stimulating the NFκB –mediated production of inflammatory cytokines (Guha et al, 2012).…”
Section: Introductionmentioning
confidence: 99%